Crossover from conserving to lossy transport in circular random-matrix ensembles. - Simon, S; Moustakas, A (2006)
In a quantum dot with three leads, the transmission matrix t12 between two of these leads is a truncation of a unitary scattering matrix S, which we treat as random. As the number of channels in the third lead is increased, the constraints from the symmetry of S become less stringent and t12 becomes closer to a matrix of complex Gaussian random numbers with no constraints. We consider the distribution of the singular values of t12, which is related to a number of physical quantities.